Id, Ego, and Superego in the Main Character of Mata di Tanah Melus Novel by Okky Madasari - Yuliana Sari; Sarwaji Suwandi; Nugraheni Eko Wardani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The purpose of this research is to explain and describe the form of id, ego, and superego in the main character in the Mata di Tanah Melus novel by Okky Madasari. The method used in this study was a descriptive method with a qualitative approach. The data source in this study was a document in the form of Mata di Tanah Melus novel by Okky Madasari, which was published by Gramedia Pustaka in 2018. The data used in this study were dialogues in the novel. The data analysis technique used in this study was the analysis of documents to find the form of id, ego, and superego in the novel. The results of this study indicate that there were forms of id, ego, and superego in Okky Madasari's Mata di Tanah Melus novel which were reflected by the main character. The forms of id, ego, and superego were found based on Sigmund Freud's personality theory. Through the form of id, ego, and superego, it can be seen how the personality of the main character in the Mata di Tanah Melus novel by Okky Madasari.